Diagnostic Accuracy of the Composite International Diagnostic Interview (CIDI 3.0) PTSD Module Among Female Vietnam‐Era Veterans. Issue 2 (April 2014) - Kimerling, Rachel; Serpi, Tracey; Weathers, Frank; Kilbourne, Amy M.; Kang, Han; Collins, Joseph F.; Cypel, Yasmin; Frayne, Susan M.; Furey, Joan; Huang, Grant D.; Reinhard, Matthew J.; Spiro, Avron; et al.
<x xml:space="preserve">Abstract</x> The World Health Organization (WHO) Composite International Diagnostic Interview (CIDI) posttraumatic stress disorder (PTSD) module is widely used in epidemiological studies of PTSD, yet relatively few data attest to the instrument's diagnostic utility. The current study evaluated the diagnostic utility of the CIDI 3.0 PTSD module with U. S. women Vietnam‐era veterans. The CIDI and the Clinician‐Administered PTSD Scale (CAPS) were independently administered to a stratified sample of 160 women, oversampled for current PTSD. Both lifetime PTSD and recent (past year) PTSD were assessed within a 3‐week interval. Forty‐five percent of the sample met criteria for a CAPS diagnosis of lifetime PTSD, and 21.9% of the sample met criteria for a CAPS diagnosis of past‐year PTSD. Using CAPS as the diagnostic criterion, the CIDI correctly classified 78.8% of cases for lifetime PTSD (κ = .56) and 82.0% of past year PTSD cases (κ = .51). Estimates of diagnostic performance for the CIDI were sensitivity of .61 and specificity of .91 for lifetime PTSD and sensitivity of .71 and specificity of .85 for past‐year PTSD. Results suggest that the CIDI has good utility for identifying PTSD, though it is a somewhat conservative indicator of lifetime PTSD as compared to the CAPS.